CI, [CII] and CO observations towards TNJ 1338-1942: Probing the ISM in a massive proto-cluster galaxy at z = 4.11 - König, S.; Greve, T.; Seymour, Nick; Rawlings, J.; Papadopoulos, P.; Ivison, R.; De Breuck, C.; Stevens, J.; Smail, I.; Kovacs, A. (2012)
A number of studies have dealt with the link between distant powerful radio sources and the most massive galaxies in the early Universe. Despite major advances in our understanding of high redshift radio galaxies (HzRGs), we still only have a rudimentary picture of the physical conditions (i.e. gas density, temperature, ambient UV-field) prevailing in the interstellar medium (ISM) of these objects. Here we report on ongoing CI, [CII] and CO observations of TNJ 1338-1942 at z 4.11 with the IRAM 30m telescope, the JCMT and ATCA. With these observations we will make a first attempt at constraining the average ISM conditions in TNJ 1338-1942.